Does the inter-osseous membrane fascial dysfunction exist ? An observational study comparing palpation to ultrasound measurements. (June 2022) - Lecardonnel, T.; Salmon, M.; Merdy, O.; Sarzeaud, R.; Matthew, T.
Abstract: Background: There is a lack of evidence to support a correspondence between osteopathic palpation and anatomical findings. The concept of dysfunction could be defined using more accurate words when describing palpatory findings if they could be explained by objective measurements. The forearm Interosseous Membrane (IOM) is a fascia often evaluated by osteopaths, searching for Fascial Dysfunction (FD). We measured IOM physical characteristics, such as elasticity and thickness, with ultrasound (US) and then compared it with osteopaths' FD assessment. Methods: Healthy subjects were recruited and their forearms were marked every centimeter. At every mark, 3 registered osteopaths assessed the potential FD (none, moderate or strong). Assessments were compared to the IOM elasticity and thickness measured by US. A mixed effect model was used to analyse the link between thickness and FD and a chi-2 test for the link between elasticity and FD. Result: 41 subjects were included. Mean age was 28.1, 46% were men. The average IOM length was 13.0 cm (±1.5), the average thickness was 1.29 (±0.41). The mixed model found a strong correlation between the grade of FD and the IOM thickness for all three osteopaths (p < 0.01). Moreover, correlations were found between thickness and elasticity of the IOM (p < 0.001). Conclusion: Manual evaluation of FD seems to be correlated to physical properties of the IOM. Our results suggest that the forearm IOM is thicker at FD locations. This study needs replications on several anatomical areas and on the IOM of symptomatic subjects to confirm these findings. Moreover, research could focus on tissue changes after osteopathic treatment.